2021
DOI: 10.5433/1679-0359.2021v42n6supl2p3581
|View full text |Cite
|
Sign up to set email alerts
|

Wheat yield and seed physiological quality as influenced by seed vigor, nitrogen fertilization and edaphoclimatic conditions

Abstract: Wheat is one of the most important cereals grown in the world, and in Brazil, increasing national production is still a challenge. Nitrogen (N) supply can favor grain yield and the physiological quality of wheat seeds. However, the definition of adequate N rate and fertilization timing must consider genotype, cultivation environment, and initial seed vigor level. The aim of this work was to evaluate the effect of initial seed vigor and the combinations of rates and timings of N application on grain yield and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
(20 reference statements)
1
7
0
Order By: Relevance
“…On the other hand, Yong et al (2004) verified that the falling number was mainly influenced by environmental factors, considering 39 wheat genotypes cultivated in four agroecological zones from China. Therefore, both factors -genotype and environmental conditions -can change the falling number, in addition to influencing other technological quality parameters of wheat flour and grain (Rozbicki et al, 2015;Souza et al, 2021;Faria et al, 2022;Martins et al, 2023), as observed in the present paper.…”
Section: Technological Quality Of Grains and Flour As Influenced By N...supporting
confidence: 54%
See 2 more Smart Citations
“…On the other hand, Yong et al (2004) verified that the falling number was mainly influenced by environmental factors, considering 39 wheat genotypes cultivated in four agroecological zones from China. Therefore, both factors -genotype and environmental conditions -can change the falling number, in addition to influencing other technological quality parameters of wheat flour and grain (Rozbicki et al, 2015;Souza et al, 2021;Faria et al, 2022;Martins et al, 2023), as observed in the present paper.…”
Section: Technological Quality Of Grains and Flour As Influenced By N...supporting
confidence: 54%
“…The alveography parameters of dough tenacity, extensibility, and P/L ratio varied mainly due to the influence of the genotype factor, which showed an interaction with the environmental conditions. This outcome is attributed to the different adaptability of each genetic material to the specific edaphoclimatic conditions (Gonçalves et al, 2020;Souza et al, 2021). Módenes et al (2009), while evaluating the rheological properties of different flours from Brazilian wheat genotypes, verified that both dough tenacity and extensibility varied according to the genotype used, but these alveography parameters were also influenced by the storage period of the wheat grains before milling, indicating that the environmental conditions can modify the alveography parameters before and after harvesting the grains.…”
Section: Technological Quality Of Grains and Flour As Influenced By N...mentioning
confidence: 98%
See 1 more Smart Citation
“…Studies carried out with plants in soils with different soil and climatic conditions are influenced by them and must be carried out to verify differences related to these contrasting conditions related to plant growth and development [ 20 ] (Moreira et al 2019). The same applies to the need to evaluate physiological characteristics in an edaphoclimatic situation different from those already studied in a temperate climate [ 21 ] (de Souza et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, excessive N rates can cause cell toxicity (Elhanafi et al, 2019), increase the severity of plant diseases such as wheat blast (Magnaporthe oryzae Triticum) (Silva et al, 2019), and, consequently, reduce wheat quality and yield. According to Souza et al (2021), unsuitable N supply impairs the physiological quality of wheat seeds, and the fertilization with 40 kg.ha −1 N at sowing (alone or combined with 40 kg.ha −1 N as topdressing fertilization at the tillering stage) resulted in the production of seeds with better physiological quality.…”
Section: Introductionmentioning
confidence: 99%